The quadry - Vignnesh, Ravindran (2023)
Electronic commerce (e-commerce) sites and applications have been the talk of the century as it is one of the most visible business uses of the World Wide Web. The primary goal of e-commerce sites and applications are to provide/sell goods and services on a virtual platform. As the world moves towards a more electronically driven environment, the implementations of e-commerce have also been on a constant rise. However, there has been resistance in local convenient and retail stores in adopting this growing technology. Hence, this project focuses on introducing the use of e-commerce technology through a cross-platform mobile application called The Quadry and its benefits such as payment gateway integration to allow customers to purchase and place orders online, automated order tracking and delivery status updates, merchant details such as location integrated with Google Maps API, operating hours, ratings, and many other features to the resisting party. Users on the other hand get to experience the simplicity and convenience of purchasing products from their local convenience stores for a relatively cheaper price than what the current ecommerce application market offers.